Skrining Anemia dengan Pemeriksaan Hemoglobin: Strategi Promotif dan Preventif untuk Peningkatan Kualitas Hidup pada Masyarakat - Herdiman, Julia; Santoso, Alexander Halim; Wijaya, Bryan Anna; Alexin, Corry Calista; Pranata, Catherine Christiana (PT. Riset Press International, 2026)
Anemia remains a major public health issue with high prevalence and substantial impact on quality of life, especially among vulnerable groups such as older adults and women. This community service program aimed to improve early anemia detection through structured hemoglobin screening combined with evidence-based health education. Conducted at Asisi Church, South Jakarta, the program involved 99 adult participants who attended health sessions and underwent hemoglobin and hematocrit assessments using point-of-care testing (POCT). Results showed that 82.82% of participants were anemic, with a mean hemoglobin of 10.89 g/dL and hematocrit of 31.71%. Women had a higher proportion of anemia and lower mean hemoglobin levels than men. These findings underscore anemia as a persistent urban health problem influenced by demographic, nutritional, lifestyle, and chronic disease factors. The program provided early identification of at-risk individuals, enhanced knowledge, and strengthened the role of community health cadres, demonstrating potential for broader replication as a promotive-preventive strategy.